The Anti-Aging Hormone Klotho Promotes Retinal Pigment Epithelium Cell Viability and Metabolism by Activating the AMPK/PGC-1α Pathway - Shuyan Zhou; Jacob Hum; Kaan Taskintuna; Stephanie Olaya; Jeremy Steinman; Junfeng Ma; Nady Golestaneh (MDPI AG, 2023)
Initially discovered by Makuto Kuro-o in 1997, Klotho is a putative aging-suppressor gene when overexpressed and accelerates aging when deleted in mice. Previously, we showed that α-Klotho regulates retinal pigment epithelium (RPE) functions and protects against oxidative stress. However, the mechanisms by which Klotho influences RPE and retinal homeostasis remain elusive. Here, by performing a series of in vitro and in vivo experiments, we demonstrate that Klotho regulates cell viability under oxidative stress, mitochondrial gene expression and activity by inducing the phosphorylation of AMPK and p38MAPK, which in turn phosphorylate and activate CREB and ATF2, respectively, triggering PGC-1α transcription. The inhibition of Klotho in human RPE cells using CRISPR-Cas9 gene editing confirmed that a lack of Klotho negatively affects RPE functions, including mitochondrial activity and cell viability. Proteomic analyses showed that myelin sheath and mitochondrial-related proteins are downregulated in the RPE/retina of Kl-/- compared to WT mice, further supporting our biochemical observations. We conclude that Klotho acts upstream of the AMPK/PGC-1α pathway and regulates RPE/retinal resistance to oxidative stress, mitochondrial function, and gene and protein expressions. Thus, KL decline during aging could negatively impact retinal health, inducing age-related retinal degeneration.